Efficiency of Low Dose Dopamine on Glomerular Filtration Rate of Dogs with Chronic Renal Failure - Srirattanaprateep, Komsan; Lekcharoensuk, Chalermpol (Journal of Mahanakorn Veterinary Medicine, 2018)
Normally, low dose dopamine is the popular medication used for treatment of the oliguric and anuric condition in dogs. The effect of low dose dopamine is for increase of diuretic potency resulted in increased elimination of waste products and other substances from the body. However, the evidences to support the diuretic potency of dopamine are inconclusive, especially in dogs with chronic renal failure. Objective of this study was to evaluate the effect of 1 µg/kg/min of dopamine on diuretic induction and increase of glomerular filtration rate (GFR). The records of 13 dogs with chronic renal failure admitted to critical care unit, Kasetsart Veterinary Teaching Hospital, Bangkhen were studied. The creatinine clearance, systolic blood pressure and water out to water in ratio from each dog were used to compare during the period of without and with dopamine administration. The generalized linear model with cross-over analysis was used with the commercial statistical software (NCSS 2007®). The results indicated that creatinine clearance during without and with dopamine administration was 0.43 ± 0.25 ml/min and 0.44 ± 0.30 ml/min, respectively (P = 0.9063). Also, systolic blood pressure during without and with dopamine administration was 127.30 ± 20.68 mm. Hg and 129.23 ± 28.71 mm. Hg, respectively (P = 0.7465). Likewise, water out to water in ratio during without and with dopamine administration was 1.01 ± 0.20 and 1.00 ± 0.27, respectively (P = 0.4733). In conclusion, administration of 1 µg/kg/min dopamine had no effect on creatinine clearance, systolic blood pressure and water out to water in ratio. Therefore, dosage of 1 µg/kg/min of dopamine could not increase diuresis and GFR.